The impact of indoor air pollution on children’s health and well-being: the experts’ consensus - Elena Bozzola; Rino Agostiniani; Laura Pacifici Noja; Jibin Park; Paolo Lauriola; Tiziana Nicoletti; Domenica Taruscio; Giovanni Taruscio; Alberto Mantovani (Italian Journal of Pediatrics, 2024)
Abstract Background Pollution of the indoor environment represents a concern for human health, mainly in case of prolonged exposure such as in the case of women, children, the elderly, and the chronically ill, who spend most of their time in closed environments. Main body The aim of the study is to organize a group of experts in order to evaluate the evidence and discuss the main risk factors concerning indoor air and the impact on human health as well as challenging factors regarding preventive strategies to reduce pollution. The experts highlighted the main risk factors concerning indoor air, including poor ventilation, climatic conditions, chemical substances, and socio-economic status. They discussed the impact on human health in terms of mortality and morbidity, as well as challenging factors regarding preventive strategies to reduce pollution. Conclusion The experts identified strategies that can be reinforced to reduce indoor pollution and prevent negative consequences on human health at national and local levels.